Arabic Speaking Skill Learning Using Word Chain Game in Madrasah - Sri Wahyuni; Mahyudin Ritonga; Reni Fitriani; Hendri Pitrianto; Zalika Adam (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
This study aimed to reveal the use of word-chain games as a strategy in teaching Arabic spaking skill (maharah al-kalam) . This study used a qualitative approach where data were collected through observation, interviews, and documentation studies. The qualitative analysis methodologies of Miles and Huberman were used for this study. Qualitative analysis consists of three steps after data collection: data condensation, data presentation, and conclusion drawing or verification. Based on the results, maharah al-kalam learning using word chain games has an impact on the quality of the process, as evidenced by increased results. Students become more active, and their motivation increases. Improving the quality of the learning process is evidenced by the active participation of students in responding to teacher statements as well as their enthusiasm in perfecting sentences spoken by other groups. Learning outcomes are getting better, but fluency and memorization of vocabulary cannot be improved using the word chain game. According to observers and practitioners of Arabic language education, word chains have an impact on teaching speaking skills; therefore, it is important to explain their use in Ilamic Junior High School (Madrasah Tsanawiyah).